Thermal Characteristic of Fire Resistance Electrical Cable for Residential Wiring Installation - Sari, Yunita (University of Muhammadiyah Malang, 2018)
The objective of the research was to investigate thermal characteristic of electrical cable for residential wiring installation in order to acquire the initial data for fire protection study especially connected to short circuit. The research methods were testing the characteristic of cable by differential scanning calorimetry (DSC), fire resistant test, and current injection test according to International Standard IEC 60332-1-1. The results of the test were: differential scanning calorimetry gave the flame temperature of the cable was 3100C, fire resistant test shown the length of charred/melted cable was 65 mm and fire was extinguished in 10 s after the source of flame was cut, the current injection test showed that for current of 60 A, the cable started to melted and produce smoke after 270 s. The result showed that the cable comply with the specification, i.e. flame retardant cable or fire resistance cable as proved by test results and can be concluded that the cable gives adequate protection to the fire. Also, it can concluded that whenever short circuits occur, the cable able to withstand the high current and temperature for prolonged time and may only resulted in charred or melted only and doesnt make the cable came into flame/fire. Even if the fire is occurred in the cable as results of short circuit, the propagation is relatively not existed.